2014
DOI: 10.1002/ejsp.2065
|View full text |Cite
|
Sign up to set email alerts
|

Too tired to taint the truth: Ego‐depletion reduces other‐benefiting dishonesty

Abstract: Numerous studies indicate that ego‐depletion increases the occurrence of self‐benefiting dishonest behavior by undermining resistance to short‐term temptations associated with dishonesty. Turning this phenomenon around, we examined whether ego‐depletion can, counterintuitively, reduce dishonest behavior in a context where dishonesty serves to benefit others. Specifically, based on the notion that ego‐depletion reduces commitment to long‐term/abstract goals and interferes with self‐control, we proposed and foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…In contrast, when monetary incentives were provided, ego‐depletion even increased dishonest behaviors that required more effort. These results are consistent with a previous study that found that ego depletion reduces other‐benefiting dishonesty (Cantarero & van Tilburg, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, when monetary incentives were provided, ego‐depletion even increased dishonest behaviors that required more effort. These results are consistent with a previous study that found that ego depletion reduces other‐benefiting dishonesty (Cantarero & van Tilburg, ).…”
Section: Discussionsupporting
confidence: 93%
“…Those in the ego‐depletion condition were asked to cross out all instances of the letter e except when the e was directly adjacent to another vowel or separated from it by only a single consonant. This manipulation has been used in previous studies and is known to be valid (Baumeister et al ., ; Cantarero & van Tilburg, )…”
Section: Methodsmentioning
confidence: 99%
“…Only one study implemented Pareto white lies (Cappelen et al, 2013) and another one investigated altruistic white lies (Maréchal et al, 2017). Another study explored the role of ego-depletion on the proclivity to tell an altruistic white lie in hypothetical situations (Cantarero &Van Tilburg, 2014).…”
Section: Outlook and Open Problemsmentioning
confidence: 99%
“…When people use self‐control, do they subsequently seek to gratify selfish desires, grabbing what they can for themselves? Much research would seem to suggest so (Achtziger, Alós‐Ferrer, & Wagner, ; Halali, Bereby‐Meyer, & Ockenfels, ; Moore & Loewenstein, ; Osgood & Muraven, ; Gino, Schweitzer, Mead, & Ariely, ; Mead, Baumeister, Gino, Schweitzer, & Ariely, ; Cantarero & Tilburg, ; Vohs, Baumeister, & Ciarocco, ; DeWall, Baumeister, Gailliot, & Maner, ). Some of us began with that hypothesis but were led to entertain a competing hypothesis.…”
Section: Selfishness Hypothesismentioning
confidence: 99%
“…Depleted people score higher than others on narcissism, a state characterized by inflated self‐views and a strong sense of entitlement to obtain what they want (Vohs et al, ). They show heightened willingness to lie and cheat in order to acquire money (Gino et al, ; Mead et al, ), but they are less likely to be dishonest when it would benefit others (Cantarero & Tilburg, ). An increase in indulging one's own needs is accompanied by a decreased concern for others, such as a reduction in helping (DeWall et al, ).…”
Section: Selfishness Hypothesismentioning
confidence: 99%